The Effect of Management Performance on The Satisfaction of Members of The Shari'ah Perambabulan Al Qomariyah Cooperative - Agus Mulyana, Andry; Cuswanto, Cuswanto; Suwarno Putra, Panji; Faqih, Achmad; Aisyah, Siti (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
The presence of sharia cooperatives provides many opportunities for the community in running their business or business. Sharia cooperatives are able to improve the welfare of people who run their businesses or businesses. If the business has sufficient capital, the business actor is able to develop his business. Sharia cooperatives can also improve the wheels of a country's economy. Member satisfaction with services is influenced by the performance of the management, satisfaction is achieved when the services received are in accordance with expectations. However, the large number of cooperative members tends not to be able to meet the expectations of all members. This study aims to determine the performance of the management on the satisfaction of members of the Syari'ah Perambabulan Al Qomariyah Cooperative in Babadan Village, Gunung Jati District, Cirebon Regency. The study was conducted from November 2022 to January 2023. The research design used was quantitative descriptive with data collection through interviews with instruments. The respondents were members of the 50-member Al Qomariyah Sharia Perambabulan Cooperative. Data analysis uses descriptive analysis and simple linear regression. The results showed that descriptively the level of management performance was at a satisfactory level by meeting the elements of tangible, reability, responsiveness, assurance and empathy percentage of 75%. Meanwhile, the satisfaction of members of the Shari'ah Perambabulan Al Qomariyah Cooperative is at a very satisfactory level with a percentage of 84%. The performance of the management affects the satisfaction of members of the Shari'ah Perambabulan Al Qomariyah Cooperative with the value of the coefficient of determination having a proportion of 19.5%. The simple linear regression equation is Y = 39.811+0.242X+e, meaning that it has a constant of 39.811 and a coefficient of 0.242 which states that every 1% increase in performance can increase satisfaction by 0.242.